An Increased Presence of Male Personalities in Dissociative Identity Disorder after Initiating Testosterone Therapy. (5th October 2020) - Mun, Monique; Gautam, Mohan; Maan, Renee; Krayem, Bassem
Abstract : Patients with gender dysphoria (GD) report significant dissociative symptoms and are found to have a high prevalence of a dissociative disorder of any kind. When GD patients elect to undergo cross-sex hormone therapy, there is a significant reduction in dissociative symptoms. However, to the best of our knowledge, there are no known case reports that describe an alteration of personalities in dissociative identity disorder after initiating cross-sex hormone therapy. Thus, we present a case of a 20-year-old transgender male with GD, whom after initiating cross-sex hormone therapy with testosterone experienced an increased presence of his existing male personalities.